(untitled) (Journal on studies and research of academic knowledge, 2024)
This research addresses the contribution of pedagogical projects to the teaching work and its impact on the learning process of middle school students in the district of Cambyretá during the 2018 school year; the importance of the work lies in the fact that pedagogical projects, are presented as work methodologies to encourage students’ learning process, promoting their creativity, curiosity, teamwork and the solution of everyday and concrete problems to achieve significant learning. The objective was to determine the contribution of pedagogical projects as a didactic strategy for the development of learning processes in middle school students in the district of Cambyretá. The methodology was quantitative, descriptive and cross-sectional. The population studied included 631 students; the sample was 309 students who were selected using statistical technique with a confidence level of 95%. The most relevant results indicate that the projects are methodological proposals that benefit the strengthening of teamwork, meaningful learning, cooperation and academic performance. The teachers accompany the elaboration and execution of the project, but do not apply the project methodology efficiently and effectively.